Halalkalibacterium roseum gen. nov., sp. nov., a new member of the family Balneolaceae isolated from soil. Issue 4 (28th April 2022) - Wu, Shuge; Wang, Jingjing; Wang, Jianing; Du, Xinran; Ran, Qi; Chen, Qi; Sheng, Duohong; Li, Yue-zhong
Abstract : A Gram-stain-negative, non-motile, moderately halophilic and facultatively anaerobic bacterium, designated YR4-1 T, was isolated from a saline-alkali and sorghum-planting soil sample collected in Dongying, Shandong Province, PR China. Growth occurred at 28–45 °C with the presence of 4.0–20.0 % (w/v) NaCl and pH 6.0–9.0. Phylogenetic analysis based on the 16S rRNA gene sequences revealed that YR4-1 T shared the highest similarity of 92.1–92.4 % with the valid published species of Aliifodinibius . The isolate formed a separate clade at the genus level in recently described family Balneolaceae . The draft genome of strain YR4-1 T is 3.83 Mbp long with 44.0 mol% G+C content. The strain possesses several genes involved in the osmotic stress response mechanism and diverse metabolic pathways, probably for the living in saline environment. This may lead to a better understanding of the underrepresented Balneolaceae lineage. The major menaquinone was MK-7. The main polar lipid profile was composed of diphosphatidylglycerol, phosphatidylglycerol, phosphoglycolipids, aminophosphoglycolipid, one glycolipid, and four unidentified lipids. The predominant cellular fatty acids were iso-C15 : 0 (35.7 %) and anteiso-C15 : 0 (33.5 %). On the basis of its phenotypic, chemotaxonomic and phylogenetic features, strain YR4-1 T represents a novel species of a new genus, for which the name Halalkalibacterium roseum gen. nov., sp. nov. is proposed. The type strain is YR4-1 T (=CGMCC 1.17777 T =KCTC 72795 T ).